Profil aktivace receptorových tyrozinkináz a mitogenem aktivovaných proteinkináz v terapii Maffucciho syndromu - Melichárková, K; Neradil, J; Múdry, P; Zitterbart, K; Obermannová, R; Skotáková, J; Veselská, R; Štěrba, J (Klinicka onkologie, 2015)
BACKGROUND: Maffucci syndrome is a rare congenital nonhereditary disease characterized by multiple hemangiomas and enchondromas, which may progress into malignancy. The causal therapy does not exist, and therapy is aimed at complications. The determination of appropriate therapy is complicated, and a multidisciplinary approach is often essential. CASE: Authors are presenting the case of a 20-year -old patient with Maffucci syndrome. During her life, multiple enchondromas and progressing hemangiomas have been revealed and they have caused many complications, such as limited movement, growth failure, pain, fluidothorax and ascites. A profile of phosphorylation of selected tyrosine kinases and MAP kinases from progressing hemangioma was performed and with consideration of the result, it led to change of treatment strategy with encouraging clinical response lasting for six months.
Keywords: Protein-Tyrosine Kinases; mitogenem aktivované proteinkinasy; tyrosinkinasy; Mitogen-Activated Protein Kinases; Enzyme Activation; enchondromatóza; ženské pohlaví; fosforylace; dospělí; Humans; Adult; Female; Phosphorylation; lidé; Enchondromatosis; aktivace enzymů